Dosimetry and toxicity outcomes in postoperative high-dose-rate intracavitary brachytherapy for endometrial carcinoma - Donnelly, Eric D. (Termedia Publishing House, 2012)
PURPOSE: The optimal dosimetric parameters and planning techniques for high-dose-rate vaginal brachytherapy (HDR-VB) are unclear. Our aim was to evaluate the utility of bladder and rectal dosimetry for patients receiving HDR-VB for postoperative treatment of endometrial carcinoma. MATERIAL AND METHODS: Patients with endometrial cancer who underwent postoperative HDR-VB from January 1, 2004 through December 31, 2010 were included. All patients underwent primary surgery consisting of total hysterectomy and bilateral salpingo-oophrectomy (TH-BSO) with or without lymph node dissection and were treated with HDR-VB without pelvic external beam radiotherapy (EBRT) or chemotherapy. Demographic, pathologic, dosimetric and clinical data were collected. RESULTS: One hundred patients were identified with the majority of patients receiving HDR-VB in 700 cGy × 3 fractions (45%) or 550 cGy x 4 fractions (53%). No plan was altered based on bladder dosimetry at the time of planning. The rate of acute urinary reactions (< 90 days from beginning of RT) grades 1 and 2 were 14% and 2%, respectively. The rate of late urinary reactions (> 90 days after RT) grades 1 and 2 were 7% and 3%, respectively. Dose to the bladder point did not correlate with urinary toxicity. No rectal toxicity was reported by patients receiving HDR-VB. CONCLUSIONS: In the setting of HDR-VB without EBRT, the measured dose to the bladder point does not predict urinary toxicity and is very unlikely to indicate the need to change the treatment plan. The treatment of endometrial carcinoma utilizing HDR-VB alone is associated with very low rates of high-grade acute or late bladder toxicity.